Effectiveness of Acceptance and Commitment Therapy on Sexual Self-Esteem, Emotional Skillfulness and Marital Adjustment in Veterans' Wives - Z. Pirani; M. Abbasi; M. Kalvani; M. Nourbakhsh (Afarand Scholarly Publishing Institute, 2017)
Aims: Due to many marital psychological problems and many stressful mental conditions, the quality of life of the veterans' spouses decreases. The aim of the study was to investigate the effects of acceptance and commitment therapy (ACT) on the sexual self-esteem, alexithymia, and marital adjustment in the veterans' spouses. Materials & Methods: In the controlled pretest-posttest semi-experimental applied study, 40 veterans' spouses of Arak were studied in 2015. The subjects, selected via available sampling method, were randomly divided into two groups including experimental and control groups (n=20 persons per group).  Data was collected using women's sexual self-esteem index (SSEL-W-SF), Locke-Wallace marital adjustment, and Toronto alexithymia scale (TAS-20). Ten ACT sessions were conducted in experimental group, while control group received no intervention. Pretest and posttest were conducted in both groups. Data was analyzed by SPSS 23 software using descriptive statistics and one-variable covariance analysis test. Findings: After the intervention, the mean scores of sexual self-esteem and marital adjustment significantly increased, while the mean score of alexithymia significantly decreased in experimental group compared to control group (p<0.001). Conclusion: The ACT increases sexual self-esteem and marital adjustment, while reduces the alexithymia in the veterans' spouses.